On the feasibility and usefulness of high-performance computing in probabilistic volcanic hazard assessment: An application to tephra hazard from Campi Flegrei - Montesinos, Beatriz Martínez; Luzón, Manuel Titos; Sandri, Laura; Rudyy, Oleksandr; Cheptsov, Alexey; Macedonio, Giovanni; Folch, Arnau; Barsotti, Sara; Selva, Jacopo; Costa, Antonio (Frontiers in Earth Science, 2022)
For active volcanoes, knowledge about probabilities of eruption and impacted areas becomes valuable information for decision-makers to develop short- and long-term emergency plans, for which Probabilistic Volcanic Hazard Assessment (PVHA) is needed. High-resolution or spatially-extended-PVHA requires extreme-scale High Performance Computing Systems. Within the framework of ChEESE (Center of Excellence for Exascale in Solid Earth, an effort was made to generate exascale-suitable codes and workflows to collect and process in some hours the large amount of data that a quality PVHA requires. To this end, we created an optimized HPC-based workflow coined PVHA_HPC-WF to develop PVHA for a volcano. This tool uses the Bayesian Event Tree methodology to calculate eruption probabilities, vent opening location(s), and Eruptive Source Parameters (ESPs) based on volcano history, monitoring system data, and meteorological conditions. Then, the tool interacts with the chosen hazard model, performing a simulation for each ESPs set or Volcanic Scenario (VS) and, finally, the resulting information is processed by Proof-of-Concept-subjected High Performance Data Analytics (HPDA)-scripts, producing the hazard maps which describe the probability over time of exceeding critical thresholds at each location on the investigated geographical domain. Although PVHA_HPC-WF can be adapted to other hazards, we focus here on tephra (i.e. lapilli and ash) transport and deposition. As an application, we performed PVHA for Campi Flegrei (CF), Italy, an active volcano located in one of the most densely inhabited areas in Europe and under busy air traffic routes. CF is currently in unrest, classified as being in an Attention Level by the Italian Civil Protection. We consider an approximate 2000x2000x40km computational domain with 2km grid resolution in the horizontal and 40 vertical levels, centered in CF. To explore the natural variability and uncertainty on the eruptive conditions we consider a large number of VSs allowing us to include those of low probability but high impact and simulations of tephra dispersal are performed for each of them using the FALL3D model. Results show the potential of HPC to timely execute a vast range of simulations of complex numerical models in large-high-resolution computational domains and analyse great volumes of data to obtain quality hazard maps.